TEACHER TALK AND LEARNING OPPORTUNITIES (A Case Study of a Pre-Service Teacher in EFL Classroom) - Juliantika Widya (Journal of English and Education, 2015)
The background of this research stemmed from the issue of significant role of teacher talk in promoting students’ learning opportunities. It was found how teacher interruptions made students had fewer learning opportunities as the teacher became dominant and took over the discussion. Thus, this research was intended to investigate the types of teacher talk produced and its influence towards students’ learning opportunities. The research was conducted in an EFL classroom of one public junior high school in Bandung by involving a pre-service teacher as the participant. The research employed a qualitative case study design in which the data were collected through video-taping, field notes, and teacher talk checklist. The analysis of the teacher talk employed the CA (Conversation Analysis) methodology while the influence of teacher talk was analyzed from field notes transcription. The research found that the most frequent type of teacher talk occurred was construction type which increased the learning opportunities for students. Further analysis on the influence of the teacher talk showed how teacher’s ability to manage the classroom and develop a good relationship through controlling the teacher talk had successfully maintained the flow of interaction in the classroom.